2017
DOI: 10.1016/j.jconrel.2017.04.025
|View full text |Cite
|
Sign up to set email alerts
|

Investigating in vitro and in vivo αvβ6 integrin receptor-targeting liposomal alendronate for combinatory γδ T cell immunotherapy

Abstract: The αvβ6 integrin receptor has been shown to be overexpressed on many types of cancer cells, resulting in a more pro-invasive and aggressive phenotype, this makes it an attractive target for selective drug delivery. In tumours that over-express the αvβ6 receptor, cellular uptake of liposomes can be enhanced using ligand-targeted liposomes. It has previously been shown in both in vitro and in vivo studies that liposomal alendronate (L-ALD) can sensitise cancer cells to destruction by Vγ9Vδ2 T cells. It is hypot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 44 publications
2
32
0
Order By: Relevance
“…zoledronate, alendronate or pamidronate) or 20.1 mAb [121] generally promoted Vγ9Vδ2 T cell mediated tumor killing, there appears to be some variability in the requirement for additional external stimuli. The majority of reports involving solid tumors suggest a stronger dependence on BTN3A agonism [50,147,[149][150][151][153][154][155] than hematologic tumors [156][157][158][159].…”
Section: Preclinical Modelingmentioning
confidence: 99%
“…zoledronate, alendronate or pamidronate) or 20.1 mAb [121] generally promoted Vγ9Vδ2 T cell mediated tumor killing, there appears to be some variability in the requirement for additional external stimuli. The majority of reports involving solid tumors suggest a stronger dependence on BTN3A agonism [50,147,[149][150][151][153][154][155] than hematologic tumors [156][157][158][159].…”
Section: Preclinical Modelingmentioning
confidence: 99%
“…Using an ovarian tumour model established by intraperitoneal (IP) inoculation, liposomal alendronate (L-ALD) has been shown to be more effective at slowing tumour growth than ALD when administered intravenously in combination with Vγ9Vδ2 T cells that were injected into the peritoneal cavity of mice [9]. Additionally, we have recently reported that only the combinatory treatment of L-ALD and γδ T cells led to a significant reduction in tumour growth in the experimental metastatic lung melanoma model, after 3 successive intravenous injections [20,21].…”
Section: Ivyspringmentioning
confidence: 99%
“…Lipid stock solutions were prepared in chloroform/methanol (4:1 v/v) at concentrations of 20-40 mg/ml and were stored under nitrogen at -20°C to avoid degradation. Alendronic acid liposomes (L-ALD) were prepared by the thin film hydration (TFH) method as previously described [20,21,25]. DSPC, cholesterol and DSPE-PEG2000 (55:40:5 molar volume) were added to a 25 ml round-bottom flask and 2 ml chloroform/ methanol (4:1 v/v) was added.…”
Section: Preparation Of Liposomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Another non-RGD pentapeptide derived from the synergy domain of fibronectin is Ac-PHSCN-NH 2 , which was clinically developed under the trade name ATN-161 for the treatment of several solid tumors [36,108] due to its high affinity for α5β1-integrin and relatively lower affinity for αvβ3and αvβ5-integrins [109]. Other integrin-targeted peptidomimetics, including SCH221153 (αvβ3-and αvβ5-integrin specific), BCH-15046 (αvβ3-, αvβ5-, and α5β1-integrin specific), SJ749 (α5β1-integrin specific), JSM6427 (α5β1-integrin specific), and A20FMDV2 (αvβ6-integrin specific), have been developed, and these have shown anticancer activities in preclinical models and when used on NPs [110,111].…”
Section: Non-rgd Integrin-targeted Ligandsmentioning
confidence: 99%